Adsorption of phenol and bisphenol-A by activated carbon and graphene oxide: a comparative study - Amina BiBi (17679402) (2025)
The adsorption of phenol and bisphenol-A (BPA), two prominent environmental pollutants, by two distinct adsorbents—activated carbon (AC) and graphene oxide (GO)—was investigated through a comparative study. Batch adsorption experiments were conducted to evaluate and compare the adsorption capacities of AC and GO for phenol and bisphenol-A removal from water. The adsorbent characterization was done using various physicochemical studies, including FTIR, SEM, TEM, RAMAN spectroscopy, and BET surface area analysis. The effects of various experimental parameters, including pH, initial pollutant concentration, temperature, and ionic strength, were examined to explain the adsorption mechanisms and optimize conditions for efficient phenol removal. The results showed that both AC and GO exhibited adsorption capacities for phenol and bisphenol-A removal, with AC showing more resilience at various experimental conditions. The maximum adsorption capacities reached approximately 39.37 mg/g for phenol and 172.41 mg/g for BPA on AC. At the same time, GO achieved around 7.69 mg/g for phenol and 70.92 mg/g for BPA under optimal conditions. Furthermore, the comparative study provided insights into the advantages of AC and limitations of GO as adsorbents for phenol and bisphenol-A removal, highlighting their potential applications in wastewater treatment and environmental remediation efforts. Other Information Published in: Environmental Science and Pollution Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11356-025-37204-7